The effect of knowledge management on perceived software process improvement: Mediating effects of critical success factors and moderating effect of the use of information technology. Issue 4 (11th November 2019) - Chugh, Mitali; Chanderwal, Nitin; Mishra, Amar Kumar; Punia, Devendra Kumar
Abstract : Purpose: This study aims to present insights on the relationship between perceived software process improvement (PSPI) and information technology (IT)-enabled knowledge management (KM). Moreover, the study provides an understanding of the mediating effect of critical success factors (CSFs) for effective IT-enabled KM on the previously mentioned relationship. Design/methodology/approach: The respondents in the study involved employees in the software engineering (SE) organizations in national capital region in India. The structured equation modeling technique carried out through IBM.SPSS.Amos.v21-EQUiNOX was used to develop and evaluate the proposed framework. The proposed hypothesis testing has been carried out by path analysis using SPSS process macro. Findings: The findings of the empirical study reveal that a significant relationship exists between the variables under investigation. Moreover, it was observed that CSFs act as a mediator between PSPI and IT-enabled KM. The identified factors are associated with various aspects as managerial, infrastructure, financial, systems and processes for IT-enabled KM. IT acts as a moderator between KM and PSPI and facilitate the various phases of KM as knowledge creation, storage and retrieval, sharing and application of knowledge. Practical implications: The present study introduces a framework for identifying and applying the CSFs that influence the KM initiatives for PSPI in an SE organization. The practitioners can use the CSFs for assessing the performance (strengths and weaknesses) in process of software development and KM practices. Researchers can use the resultant framework proposed in the empirical study for PSPI, IT-enabled KM, and in academia, the framework supports to organize the study of IT-enabled KM for PSPI. Originality/value: The general comprehension of the relationship between IT-enabled KM and PSPI for Indian SE organizations is scarce in the literature. Following, the analysis expands the earlier research by exploring the mediating role of the CSFs and the moderating effect of IT for KM and PSPI relationship.